Defending Western Civilization according to Samuel Huntington - Rechlewicz, Wojciech (Sensus Historiae, 2020)
According to Samuel Huntington, one of the greatest threats posed to the West is the loss of cultural identity. This phenomenon is connected with the questioning of the so-called American Creed in the United States (which includes such values as: freedom, democracy, individualism, equality before the law, constitutionalism, private property) and national identity based on it in favor of the belief in the equality of all cultures and the cultivation of subnational identities. Huntington believes that the West should deepen its internal integration, renew its identity and strengthen its own culture, but, at the same time, must refrain from promoting it in other cultural circles and refrain from interfering in the affairs of other civilizations. However, in the face of the threats facing the world (global warming, migration, terrorism), it is not so much the defense of Western civilization that is needed, but rather cooperation between civilizations based on common values.